A relatively mild phenotype associated with mutation of SCN8A. (March 2018) - Bagnasco, Irene; Dassi, Patrizia; Blé, Roberta; Vigliano, Piernanda
Abstract: Mutations in SCN8A gene have been described in relation to infantile onset epilepsy with movement disorders and developmental delay. Recently various authors have reported patients carrying autosomal dominant heterozygous SCN8A mutations and a milder phenotype expression. We discuss the case of a 6-year-old girl with a positive family history for epilepsy, early benign focal epilepsy, well controlled by Carbamazepine, upper limb tremor since birth, ataxia, slight motor delay and normal cognitive development. Neuroradiological study is normal, waking EEGs are normal, while epileptiform abnormalities on the vertex appear during sleep. The girl carries a de novo mutation of the SCN8A gene with nucleotide substitution of c.3943G > A (p.Val 1315 Met), located in the domain III S4/S5 intracellular linker. In literature two other cases with the same mutation have been reported, both patients have an epileptic encephalopathy. Our patient's milder phenotype could be caused by a modifier effect, possibly a mutation in another gene or a mosaicism. The detailed description of our case should contribute to enlarging the description of the clinical features of SCN8A mutations and to recommending the deepening of genetic investigations to